Ultrafiltration hydrophilic coating and preparation method thereof

By coating the ultrafiltration hydrophilic coating of carboxylic acid groups containing hydrophilic polymers, amino crosslinkers and zirconia nanoparticles on the surface of the ultrafiltration membrane, the problem of easy adsorption of hydrophobic substances in the ultrafiltration membrane is solved, and the ultrafiltration membrane is realized is achieved. It has higher anti-pollution ability and longer membrane life, improving processing efficiency and economic benefits.

CN119455689APending Publication Date: 2025-02-18JIANGSU BANGTEC ENVIRONMENTAL SCI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411559011.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Due to the hydrophobic properties of its material, ultrafiltration membranes are prone to adsorbing and aggregating hydrophobic substances, forming a stubborn pollutant gel layer, hindering the passage of water, resulting in a decrease in membrane flux, an increase in operating pressure, a shortened service life and an increase in operating costs.

Method used

Using an ultrafiltration hydrophilic coating, including hydrophilic polymer containing carboxylic acid groups, amino crosslinking agent and zirconia nanoparticles, a uniformly dispersed solution is prepared by high-speed dispersion and stirring, and applied to the surface of the ultrafiltration membrane. And it is cross-linked by extrusion rollers to form a hydrophilic coating.

Benefits of technology

Effectively prevent the adsorption of pollutants on the surface of ultrafiltration membrane, improve anti-pollution ability, extend membrane life, ensure system stability, improve membrane permeability flux, reduce energy consumption, and broaden the application range of ultrafiltration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455689A_ABST
    Figure CN119455689A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrafiltration hydrophilic coating. The ultrafiltration hydrophilic coating comprises the following components: a hydrophilic polymer containing a carboxylic acid group, an amino crosslinking agent and zirconium oxide nanoparticles, the ultrafiltration hydrophilic coating comprises the following components in parts by weight: 0.4-0.6 part of a hydrophilic polymer containing a carboxylic acid group; 0.4 to 0.6 part of an amino crosslinking agent; and 0.02 to 0.2 part of zirconium oxide nano particles. The invention also discloses a preparation method of the ultrafiltration hydrophilic coating, which comprises the following steps: S1, mixing the hydrophilic polymer containing the carboxylic acid group, the amino cross-linking agent and the zirconium oxide nanoparticles, and dispersing and stirring at a high speed of 2000rpm for 6 hours to prepare a fixed and uniformly dispersed solution; s2, uniformly coating the surface of an ultrafiltration membrane with the fixed and uniformly dispersed solution through a coating solution; and S3, extruding redundant solution through an extrusion roller, and carrying out cross-linking curing to prepare the ultrafiltration hydrophilic coating. Adsorption of pollutants on the surface of the ultrafiltration membrane can be effectively prevented, the anti-pollution capacity is improved, the service life of the membrane is prolonged, and system stability is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultrafiltration hydrophilic coating and a preparation method thereof. Background Art

[0002] Ultrafiltration technology is widely used in the industrial field. As an efficient membrane separation method, it can effectively treat industrial wastewater, remove suspended solids, colloids and some macromolecular pollutants, and realize the recycling of water resources. At the same time, in the pharmaceutical, food and biotechnology industries, ultrafiltration technology also plays a key role in purifying, concentrating and separating products to ensure product quality and safety. It is easy to operate, has low energy consumption and significant environmental benefits, making it one of the important technologies to promote the green transformation of industry.

[0003] However, in actual applications, ultrafiltration membranes, due to the hydrophobic properties of their materials, easily adsorb and aggregate hydrophobic substances on the surface, such as organic matter, protein, oil and other pollutants, forming a stubborn pollutant gel layer, which seriously hinders the passage of water, resulting in a decrease in membrane flux, an increase in operating pressure, a shortened service life and an increase in operating costs.

[0004] In traditional technical solutions, the most common method of hydrophilic modification is to use UV or plasma technology to form free radicals on the surface, and use surface grafting hydrophilic groups to achieve permanent surface hydrophilic modification; however, this requires expensive equipment investment, and due to the limited number of surface grafted groups, it is not suitable for oil-water separation applications. Oil droplets will still adsorb on the membrane surface, and superoleophobic properties cannot be achieved.

[0005] In order to solve this problem, it is necessary to improve the surface properties of the membrane through technical means such as hydrophilic modification so that it can repel pollutants such as oil and protein, thereby proposing an ultrafiltration hydrophilic coating and its preparation method. Summary of the invention

[0006] The purpose of the present invention is to overcome the existing defects and provide an ultrafiltration hydrophilic coating and a preparation method thereof, which can effectively prevent the adsorption of pollutants on the surface of the ultrafiltration membrane, improve the anti-pollution ability, extend the membrane life, and ensure the stability of the system.

[0007] The technical solution to achieve the above purpose is: An ultrafiltration hydrophilic coating according to one embodiment of the present invention comprises the following components: a hydrophilic polymer containing a carboxylic acid group, an amino cross-linking agent and zirconium oxide nanoparticles; The ultrafiltration hydrophilic coating comprises the following components by weight: 0.4-0.6 parts of a hydrophilic polymer containing a carboxylic acid group; 0.4-0.6 parts of amino crosslinking agent; Zirconia nanoparticles 0.02-0.2 parts.

[0008] Preferably, the hydrophilic polymer contains, in addition to the carboxylic acid group, a sulfonic acid group or a phosphoric acid group with an organic acid group having a pKa>2.

[0009] Preferably, the hydrophilic polymer includes, but is not limited to: copolymers of polyacrylic acid and maleic anhydride, copolymers of acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid, terpolymers of carboxylic acid-sulfonic acid-acrylate, polyepoxysuccinic acid and polyaspartic acid; wherein the molecular weight of the polymer ranges from 2000 to 1000000 Daltons, and the molar ratio of carboxylic acid groups to functional groups is greater than 30%.

[0010] Preferably, the amino crosslinking agent is melamine formaldehyde resin.

[0011] Preferably, the crystal form of the zirconium oxide nanoparticles includes one or more of monoclinic, tetragonal or cubic systems, and the size range is between 30-200 nm.

[0012] A method for preparing an ultrafiltration hydrophilic coating according to the second aspect of the present invention comprises: Step S1, mixing a hydrophilic polymer containing a carboxylic acid group, an amino crosslinking agent, and zirconium oxide nanoparticles, and preparing a fixed and uniformly dispersed solution by high-speed dispersion stirring at 2000 rpm for 6 hours; Step S2, uniformly coating the fixed and uniformly dispersed solution on the surface of the ultrafiltration membrane by means of a coating liquid; Step S3, squeezing out excess solution through a squeezing roller, cross-linking and curing, and preparing an ultrafiltration hydrophilic coating.

[0013] Preferably, in step S1, the copolymer containing carboxylic acid groups, the amino crosslinking agent and the zirconium oxide nanoparticles are mixed and dispersed at a high speed of 2000 rpm for 6 hours to prepare a fixed and uniformly dispersed aqueous solution.

[0014] Preferably, in step S2, the solvent of the coating liquid is one or more of water, ethanol, and ethylene glycol monomethyl ether, the solid weight range is 0.1%-1%, and the pH is less than 4.

[0015] Preferably, in step S2, the coating method is one of flow coating, dip coating, transfer or spray coating.

[0016] Preferably, in step S3, the temperature of the cross-linking curing condition is 40-80°C.

[0017] The beneficial effects of the present invention are as follows: the ultrafiltration hydrophilic coating formed by the present invention can effectively prevent the adsorption of pollutants on the surface, improve the anti-pollution ability, extend the membrane life, and ensure the stability of the system; at the same time, the membrane permeation flux is increased after the transformation, the treatment efficiency is improved, and the energy consumption is reduced, especially in water treatment; this transformation also broadens the application scope of ultrafiltration, enabling it to cope with more complex water quality challenges; on the economic level, it reduces the cleaning frequency and energy consumption, improves the system efficiency, and brings significant cost savings and benefit improvements; the ultrafiltration hydrophilic coating effectively repels oil pollution with its unique hydrophilic and oleophobic properties, and at the same time utilizes the efficient membrane separation capacity to accurately intercept tiny oil droplets, emulsified oil and dissolved oil in oily wastewater, and realizes efficient separation of oil and water, which not only improves the effluent quality and reduces the difficulty of subsequent treatment, but also greatly improves the oil removal efficiency and stability, providing a reliable solution for industrial wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of a method for preparing an ultrafiltration hydrophilic coating of the present invention; Figure 2 Schematic diagram of the chemical formula of the copolymer of acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid in the present invention; Figure 3 is a schematic diagram of the chemical formula of the terpolymer of carboxylic acid-sulfonic acid-acrylate in the present invention; Figure 4 Schematic diagram of the chemical formula of polyepoxysuccinic acid in the present invention; Figure 5 is a schematic diagram of the chemical formula of polyaspartic acid in the present invention; Figure 6 is a schematic diagram of the chemical formula of the melamine formaldehyde resin of the present invention; Figure 7 Schematic diagram of the SEM microstructure of the surface cortex of the ultrafiltration hydrophilic coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside" and the like indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0020] The present invention will be further described below in conjunction with the accompanying drawings.

[0021] An ultrafiltration hydrophilic coating, comprising the following components: a hydrophilic polymer containing a carboxylic acid group, an amino cross-linking agent and zirconium oxide nanoparticles; The ultrafiltration hydrophilic coating comprises the following components by weight: 0.4-0.6 parts of a hydrophilic polymer containing a carboxylic acid group; 0.4-0.6 parts of amino crosslinking agent; Zirconia nanoparticles 0.02-0.2 parts.

[0022] In the embodiment, the hydrophilic polymer contains, in addition to the carboxylic acid group, an organic acid group with a pka>2 such as a sulfonic acid group or a phosphoric acid group, so as to enhance the chelating effect on the zirconium oxide nanoparticles.

[0023] In the embodiment, the hydrophilic polymer includes but is not limited to: a copolymer of polyacrylic acid-maleic anhydride, a copolymer of acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid, the chemical formula of which is as follows: Figure 2 As shown, the terpolymer of carboxylic acid-sulfonic acid-acrylate, the chemical formula is as follows Figure 3 As shown, polyepoxysuccinic acid, chemical formula is as Figure 4 As shown, polyaspartic acid, chemical formula is as Figure 5 As shown; wherein the polymer molecular weight ranges from 2000 to 1000000 Daltons, and the molar ratio of carboxylic acid groups to functional groups is greater than 30%.

[0024] In the embodiment, the amino crosslinking agent is melamine formaldehyde resin, the chemical formula of which is as follows Figure 6 shown.

[0025] In the embodiment, the crystal form of the zirconium oxide nanoparticles includes one or more of monoclinic, tetragonal or cubic systems, and the size ranges from 30 to 200 nm.

[0026] like Figure 1 As shown, a method for preparing an ultrafiltration hydrophilic coating comprises: Step S1, mixing a hydrophilic polymer containing a carboxylic acid group, an amino crosslinking agent, and zirconium oxide nanoparticles, and preparing a fixed and uniformly dispersed solution by high-speed dispersion stirring at 2000 rpm for 6 hours.

[0027] In the embodiment, a copolymer containing a carboxylic acid group, an amino crosslinking agent, and zirconium oxide nanoparticles are mixed and stirred at a high speed of 2000 rpm for 6 hours to prepare a fixed and uniformly dispersed aqueous solution.

[0028] Step S2, uniformly coating the fixed and uniformly dispersed solution on the surface of the ultrafiltration membrane by means of a coating liquid.

[0029] In the embodiment, the solvent of the coating liquid is one or more of water, ethanol, and ethylene glycol monomethyl ether, and the solid weight refers to the solid content, that is, the total weight of the hydrophilic polymer containing carboxylic acid groups, the amino crosslinking agent and the zirconium oxide nanoparticles accounts for a percentage of the solution weight in the range of 0.1%-1%, and the pH is less than 4.

[0030] In the embodiment, the coating method is one of flow coating, dip coating, transfer coating or spray coating.

[0031] Step S3, squeezing out excess solution through a squeezing roller, cross-linking and curing, and preparing an ultrafiltration hydrophilic coating.

[0032] In the embodiment, the temperature of the cross-linking curing condition is 40-80°C.

[0033] The ability of the ultrafiltration hydrophilic coating of the present invention to prevent the adsorption of pollutants on the surface of the ultrafiltration membrane was verified by the following experiment.

[0034] Comparative example: Preparation of polysulfone ultrafiltration membrane: polysulfone (molecular weight of about 50,000) and N,N-dimethylformamide are mixed at 80°C, and after stirring and degassing, a 16% uniform solution is prepared, and the temperature is cooled to 25°C; this solution is continuously coated on the non-woven fabric support layer by slit coating, and passed through an 8% NMP (N-methylpyrrolidone) aqueous solution, and phase conversion is formed to form an ultrafiltration microporous membrane with a thickness of 35μm; the pure water flux is 485LMH / bar, and the bovine serum albumin removal rate is 88.7%; the pure water surface contact angle is about 69°.

[0035] Example 1: Mix 3.0g aqueous solution of acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid copolymer, 5.0g aqueous solution of melamine formaldehyde resin and 2.3g zirconium oxide particles with a particle size of 30nm, and stir at 2000rpm for 6 hours to make a uniformly dispersed aqueous solution with a solid content of 1%. Adjust the pH value of the solution to 1.3. This solution is evenly coated on the surface of the ultrafiltration membrane by transfer printing, and the excess solution is squeezed out by a squeeze roller. The water is removed in an 80℃ oven to prepare a hydrophilic ultrafiltration; the test pure water flux is 120LMH / bar, and the bovine serum albumin removal rate is 95.6%. The pure water surface contact angle is less than 5°.

[0036] Example 2: Mix 5.0g of polyaspartic acid aqueous solution, 5.0g of melamine formaldehyde resin aqueous solution and 0.8g of 30nm zirconium oxide particles, and stir at 2000rpm for 6 hours to make a uniformly dispersed aqueous solution with a solid content of 0.2%. Adjust the pH value of the solution to 1.3. The solution is evenly coated on the surface of the ultrafiltration membrane by transfer printing, and the excess solution is squeezed out by a squeeze roller. The water is removed in an 80℃ oven to prepare a hydrophilic ultrafiltration; the test pure water flux is 288LMH / bar, and the bovine serum albumin removal rate is 92%. The pure water surface contact angle is less than 5°.

[0037] like Figure 7 As shown, the SEM of the coating surface of Example 1 shows that the zirconium oxide nanoparticles are evenly distributed on the surface and are embedded in the cross-linked polymer of the coating. By comparing the comparative example with Example 1 and Example 2, it can be concluded that the hydrophilic coating of the ultrafiltration membrane can effectively prevent oil droplets from occupying the membrane surface, while the surface of the uncoated ultrafiltration membrane is easily adsorbed with oil droplets. Once the oil droplets contaminate the surface, it will cause serious flux attenuation and is not easy to clean and recover.

[0038] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultrafiltration hydrophilic coating, characterized in that: The ultrafiltration hydrophilic coating comprises the following components: a hydrophilic polymer containing a carboxylic acid group, an amino cross-linking agent and zirconium oxide nanoparticles; The ultrafiltration hydrophilic coating comprises the following components by weight: 0.4-0.6 parts of a hydrophilic polymer containing a carboxylic acid group; 0.4-0.6 parts of amino crosslinking agent; Zirconia nanoparticles 0.02-0.2 parts.

2. An ultrafiltration hydrophilic coating according to claim 1, characterized in that: In addition to carboxylic acid groups, hydrophilic polymers also contain sulfonic acid groups or phosphoric acid groups with organic acid groups with pKa>2.

3. The ultrafiltration hydrophilic coating according to claim 1, characterized in that: The hydrophilic polymer includes, but is not limited to, a copolymer of polyacrylic acid and maleic anhydride, a copolymer of acrylic acid and 2-acrylamide-2-methylpropane sulfonic acid, a terpolymer of carboxylic acid-sulfonic acid-acrylate, polyepoxysuccinic acid and polyaspartic acid; wherein the molecular weight of the polymer ranges from 2000 to 1000000 Daltons, and the molar ratio of the carboxylic acid group to the functional group is greater than 30%.

4. The ultrafiltration hydrophilic coating according to claim 1, characterized in that: The amino crosslinking agent is melamine formaldehyde resin.

5. The ultrafiltration hydrophilic coating according to claim 1, characterized in that: The crystal form of the zirconium oxide nanoparticles includes one or more of a monoclinic system, a tetragonal system or a cubic system, and the size ranges from 30 to 200 nm.

6. A method for preparing an ultrafiltration hydrophilic coating, characterized in that: include: Step S1, mixing a hydrophilic polymer containing a carboxylic acid group, an amino crosslinking agent, and zirconium oxide nanoparticles, and preparing a fixed and uniformly dispersed solution by high-speed dispersion stirring at 2000 rpm for 6 hours; Step S2, uniformly coating the fixed and uniformly dispersed solution on the surface of the ultrafiltration membrane by means of a coating liquid; Step S3, squeezing out excess solution through a squeezing roller, cross-linking and curing, and preparing an ultrafiltration hydrophilic coating.

7. The method for preparing an ultrafiltration hydrophilic coating according to claim 6, characterized in that: In the step S1, the copolymer containing carboxylic acid groups, the amino crosslinking agent, and the zirconium oxide nanoparticles are mixed and stirred at a high speed of 2000 rpm for 6 hours to prepare a fixed and uniformly dispersed aqueous solution.

8. The method for preparing an ultrafiltration hydrophilic coating according to claim 6, characterized in that: In step S2, the solvent of the coating liquid is one or more of water, ethanol, and ethylene glycol monomethyl ether, the solid weight range is 0.1%-1%, and the pH is less than 4.

9. The method for preparing an ultrafiltration hydrophilic coating according to claim 6, characterized in that: In step S2, the coating method is one of flow coating, dip coating, transfer coating or spray coating.

10. The method for preparing an ultrafiltration hydrophilic coating according to claim 6, characterized in that: In the step S3, the cross-linking curing temperature is 40-80°C.